Answered

At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve.

1 = –(–w + 6)

A.
3

B.
–7

C.
–3

D.
7


Sagot :

luana
[tex]1=-(-w+6) \ \ \ \ | omiting\ the\ bracket\\\\ 1=w-6\ \ \ \ | add\ 6\\\\ w=7\\\\Solution\ is\ D.[/tex]
well you want to distribute the negative sign so it will be a lil easier to solve 

so  -(-w+6) becomes (w-6)

now plug in each value
 a. 3-6 = -3
b. -7-6= -13
c. -3-6= -9
d. 7-6= 1